Cultural adaptation of Indonesian diaspora in Thailand’s social contexts - Siagian, Haidir Fitra; Tike, Arifuddin (Penerbit Universiti Kebangsaan Malaysia, 2019)
As a long time friend of Indonesia, Thailand is among the countries of choice for Indonesians to live overseas. This study aims to explore the Indonesian Diaspora's perceptions regarding cultural differences between Thai and Indonesian and cultural adaptation that they experience while interacting with Thai. The study utilizes Kim’s Stress-Adaptation Growth model to explain phenomenon in the intercultural interaction between Indonesians and Thai. This is a qualitative study with nine participants consisting of two Thai citizens of Indonesian descent, and seven Indonesian residing in Thailand: four workers, and three university students. The selection of participants used a purposive sampling technique. Data were obtained through interviews and document reviews and analyzed with thematic analysis. The results of the study showed participants’ perspectives and adaptations in relation to Thai rules, norms, and customs; religious aspects; sexual attitudes and behaviors; interaction in academic space; and language issues. Even though participants experienced various cultural differences, they did not report any significant stress in adaptation process. As this study is mostly about Indonesian living in urban Thailand, it is important that future research in this topic can cover other regions of Thailand, particularly the rural one, to get more comprehensive features of intercultural interaction between Indonesian and Thailand.